OBSTACLING AND SUPPORTING FACTORS FOR THE USE OF POWER POINT-BASED INTERACTIVE LEARNING MEDIA IN PAI AT MAS AMALIYAH SUNGGAL - Fitri Amaliyah Batubara; Nurhalima Tambunan; Nanda Rahayu Agustia (Proceeding International Seminar of Islamic Studies, 2023)
Power Point-based interactive learning media is one of the media that can be used by teachers in conducting learning in class. In PAI subjects, this media can be used effectively and efficiently to help teachers achieve learning goals. As one of the media that can facilitate various needs and learning styles of students, this learning media has several other advantages, such as making it easier for users to make presentation slides, equipped with various tools, such as text art, image import, etc., various templates, can be exported to PDF, has collaboration features, etc. However, behind its advantages, Power Point has disadvantages such as only being used on the Microsoft Platform, document instability in each version, and the price is too expensive. Adhering to the advantages that exist in this media, the inhibiting factors for its use in MAS Amaliyah Sunggal are still experienced or felt by PAI teachers, such as facilities and infrastructure, in this case the number of infocus is limited so that the implementation is carried out alternately with other subject teachers. In addition, teaching staff or teachers have limited skills on how to use media in the teaching and learning process in the classroom and are not fully capable of making their own learning media. Then, not all material in the lesson can use Power Point-based interactive learning. Even so, there are supporting factors for the use of this media in the school, such as positive perceptions of teachers such as interactive learning media based on Power Point facilitating the delivery of subject matter and achieving learning objectives, attracting students' attention and interest in learning so as to make students more enthusiastic and eager to listen to learning and follow every learning step that has been prepared by the PAI teacher. In addition, the teacher has the willingness to carry out varied and interesting learning in each learning meeting. Finally, there is a school's willingness to continuously try to provide learning facilities or school facilities and infrastructure that support learning activities.